Binding of a 50-kD Protein to a U-Rich Sequence in an mRNA Encoding a Proline-Rich Protein That Is Destabilized by Fungal Elicitor. - Zhang, S. (1994)
The mRNA encoding the bean proline-rich protein PvPRP1 has been shown previously to be destabilized in elicitor-treated cells. In this study, we identified a 50-kD protein in cellular extracts that binds specifically to the PvPRP1 mRNA by UV cross-linking assays. Using 32P-labeled RNAs transcribed in vitro from a series of 5[prime] deleted PvPRP1 cDNA clones, we demonstrated that the PvPRP1 mRNA binding protein (PRP-BP) binds to a 27-nucleotide U-rich (~60%) domain in the 3[prime] untranslated region. Poly(U) and, to a lesser extent, poly(A-U) competed for the PRP-BP binding activity. PRP-BP activity is redox regulated in vitro, as shown by the effects of sulfhydryl-modifying reagents on the RNA binding activity. Treatment of cellular extracts with the reducing agents DTT and [beta]-mercaptoethanol increased binding activity, whereas treatment with the oxidizing agent diamide and the alkylating agent N-ethylmaleimide inhibited binding. In extracts from elicitor-treated cells, PRP-BP activity increased approximately fivefold prior to rapid PvPRP1 mRNA degradation. The increase in PRP-BP activity was apparently due to post-translational regulation because control and elicitor-treated cell extracts supplemented with DTT showed high comparable levels of RNA binding activity. The kinetics of PRP-BP activation after elicitor treatment and its capacity for redox regulation in vitro suggested that PRP-BP may function in the elicitor-induced destabilization of PvPRP1 mRNA.